On minimal artinian modules and minimal artinian linear groups - Leonid A. Kurdachenko; Igor Ya. Subbotin (International Journal of Mathematics and Mathematical Sciences)
The paper is devoted to the study of some important types of minimal artinian linear groups. The authors prove that in such classes of groups as hypercentral groups (so also, nilpotent and abelian groups) and FC-groups, minimal artinian linear groups have precisely the same structure as the corresponding irreducible linear groups.